Buddhist World in Global Context - Ulanov, Mergen Sandzhievich; Badmaev, Valery Nikolaevich (International Journal of Economics and Financial Issues, 2015)
The Article covers the problem of globalization process impact on the Buddhism. Authors note that Buddhism takes into consideration the spirit of time and makes attempts to modernize. Buddhism has been growing as one of the most influential elements of cultural landscape in globalization process. It may be explained by the fact that due to religious and genetics reasons Buddhism does not have organized antiglobalism. Besides, individual character of self-fulfillment, inner spiritual freedom, private character of religiousness and pluralism that are typical for Buddhist tradition are consonant with the values of global liberation cultivated now. They are human rights and freedoms, ideas of democracy and post-modernism. Keywords: Buddhism, religion, globalization, neo-Buddhism, modernization. JEL Classifications: F60; P46; Z12